Financial sector development and investment in selected countries of the Economic Community of West African States: Empirical evidence using heterogeneous panel data method - Chimere Okechukwu Iheonu; Simplice Asongu; Kingsley O. Odo; Patrick K. Ojiem (Financial Innovation, 2020)
This study investigated the impact of financial sector development on domestic investment in selected countries of the Economic Community of West African States (ECOWAS) for the years 1985-2017. The study employed the augmented mean group procedure, which accounts for country-specific heterogeneity and cross-sectional dependence, and the Granger non-causality test to test for causality in the presence of cross-sectional dependence. The results show that (1) The impact of financial sector development on domestic investment depends on the measure of financial sector development utilised; (2) Domestic credit to the private sector has a positive but insignificant impact on domestic investment in ECOWAS, whereas banking intermediation efficiency (i.e., ability of the banks to transform deposits into credit) and broad money supply negatively and significant influence domestic investment; (3) Cross-country differences exist in the impact of financial sector development on domestic investment in the selected ECOWAS countries; and (4) Domestic credit to the private sector Granger causes domestic investment in ECOWAS. The study recommends careful consideration in the measure of financial development that is utilised as a policy instrument to foster domestic investment. We also highlight the importance of employing country-specific domestic investment policies to avoid blanket policy measures. Domestic credit to the private sector should be given priority when forecasting domestic investment into the future.
Keywords: C5; E2; E5; G0; 650; Financial sector development; Domestic investment; Augmented mean group; Granger non-causality test; ECOWAS